Prioritisation of patients awaiting hip and knee arthroplasty: Lower pre‐operative EQ‐5D is associated with greater improvement in quality of life and joint function. (13th May 2022) - Farrow, Luke; Redmore, James; Talukdar, Partha; Clement, Nick; Ashcroft, George P.
Abstract: Introduction: The COVID‐19 pandemic has led to unprecedented delays for those awaiting elective hip and knee arthroplasty. Current demand far exceeds available resource, and therefore it is integral that healthcare resource is fairly rationed to those who need it most. We therefore set out to determine if pre‐operative health‐related quality of life assessment (HRQoL) could be used to triage arthroplasty waiting lists. Methods: Data regarding demographics, perioperative variables and patient reported outcome measures (PROMs) (pre‐operative and 1‐year post‐operative EuroQOL five dimension (EQ‐5D‐3L) and Oxford hip and knee scores (OHS/OKS) were retrospectively extracted from electronic patient health records at a large university teaching hospital. Patients were split into two equal groups based on pre‐operative EQ‐5D TTO scores and compared (Group1 [worse HRQoL] = −0.239 to 0.487; Group2 [better HRQoL] = 0.516–1 [best]). Results: 513 patients were included. Patients in Group1 had significantly greater improvement in post‐operative EQ‐5D‐3L scores compared to Group2 (Median 0.67 vs. 0.19; p < 0.0001), as well as greater improvement in OHS/OKS (Mean 22.4 vs. 16.4; p < 0.0001). Those in Group2 were significantly less likely to achieve the EQ‐5D‐3L minimum clinically important difference (MCID) attainment (OR 0.13, 95%CI 0.07–0.23; p < 0.0001) with a trend towards lower OHS/OKS MCID attainment (OR 0.66, 95%CI 0.37–1.19; p = 0.168). There was no clinically significant difference in length of stay (Median 3‐days both groups), and no statistically significant difference in adverse events (30 days and 1 year readmission/reoperation). Conclusions: A pre‐operative EQ‐5D‐3L cut‐off of ≤0.487 for hip and knee arthroplasty prioritisation may help to maximise clinical utility and cost‐effectiveness in a limited resource setting post COVID‐19.